Length-weight relationships for 13 fish species from the Gulf of Gabes (Southern Tunisia, Central Mediterranean) - Hajjej Ghailen; Hattour Abdallah; Allaya Hassan; Cherif Mourad; Bouain Abderrahmen; Jarboui Othman (Advances in Aquaculture and Fisheries Management, 2023)
Length-weight relationships (LWR) were estimated for 13 fish species which are of economic relevance in the commercial fisheries of the Gulf of Gabes (southern Tunisia). A total of 2403 fish specimens were sampled with several fishing gears from October 2008 to September 2009. The sample size ranged from 65 individuals for Coryphaena hippurus to 346 for Euthynnus alletteratus. The b values in the LWR, W = aLb ranged from 2.807 to 3.284, with a mean of 3.015 ± 0.102 and intercepts between 0.0011 and 0.0432 with a mean of 0.0139. The condition factor (c.f.) values significantly (p < 0.05) ranged from 0.64 to 1.55.